Kala Tatwa Dan Realisasinya Terhadap Keberagamaan Masyarakat Hindu Di Bali - Parsua, Gede Rai (Jurnal Penelitian Agama Hindu, 2025)
Bhatara Kala is commonly perceived by the general public as a terrifying, evil, and monstrous figure. However, according to the Kala Tatwa palm-leaf manuscript, Bhatara Kala is the son of Bhatara Siwa and Bhatari Giri Putri, symbolizing the manifestation of the Panca Maha Bhuta (Akasa, Apah, Teja, Bayu, Pertiwi), representing both time and cosmic energy. This study aims to deepen faith (sradha) and devotion (bhakti) to the Supreme God, and to understand the concept of kala (time) and its realization within the religious practices of the Balinese Hindu community. The research adopts a semi-literature and field-based approach, utilizing data collection methods such as observation, hermeneutics, literature review, document study, and data analysis through reduction, textual criticism, and data presentation techniques. The findings reveal that Bhatara Kala is interpreted as a symbol of time and energy that governs all existence and cannot be stopped. In Balinese Hindu belief, time is sacred and serves as the foundation for determining auspicious days (dewasa ayu) for performing religious rituals, such as Dewa Yadnya, Manusa Yadnya, Rsi Yadnya, Pitra Yadnya, and Bhuta Yadnya. The belief in Bhatara Kala reflects the community’s profound understanding of time, space, and transformation (Desa, Kala, Patra), ensuring that every spiritual activity aligns harmoniously with cosmic rhythms and the natural world.